The Fragmentation of Religious Authority: Islamic Print Media in Early 20th Century Indonesia - Burhanudin, Jajat (Studia Islamika, 2004)
Aside from the scarcity of historical sources, it is not the intention of this article to determine when the pesantren -or pesantren like institutions, namely surau in West Sumatra and dayah in Aceh- began to exist. Here, the main concern is that in the nineteenth century the pesantrens were established as the educational institutions of Indonesian Muslims. Dutch statistical sources from this period recorded that there were about fifteen thousands (15,000) pesantrens in Java and Madura, and about twenty-three thousand (23,000) santris (the students of pesantren) (van den Berg 1886: 518-9).DOI: 10.15408/sdi.v11i1.652